Modulação da resposta inflamatória e aceleração da cicatrização de feridas cutâneas experimentais pelas proteínas isoladas do látex de Himatanthus drasticus Mart. (PLUMEL) - Souza, Tamiris de Fátima Goebel de (2015)
The treatment of chronic skin wounds results in high costs and risks of complications that could delay the resolution of the healing process. In this study, a pharmaceutical formulation (ointment) was developed containing an isolated protein fraction from Himatanthus drasticus latex (HdLP) in order to investigate its effect on the excisional wound healing in swiss mice (25±3,0 g). Inicially, the dermal irritation test in mice demonstrated that topical treatment with the ointment containing HdLP was not able to cause reactions of irritation in intact skin and the damaged skinreactions. The macroscopic analysis showed that HdLP 0,5%, 1,0% and 2,0% did not affect the inflammatory signs of edema and hyperemia in excisional wounds but treatment with 2,0% HdLP accelerated contraction of ulcers from 9th day after surgical induction of injury, anticipated the appearance of scar tissue and favored a complete re-epithelialization of wounds.After macroscopic analysis, the concentration of HdLP 2,0% was chosen for the histopathological study (leukocyte infiltration, mast cell degranulation, fibroplasia and collagenesis) and inflammatory mediators (myeloperoxidase (MPO), levels of nitrite and pro- and anti-inflammatory cytokines (TNF-α, IL-1β, IL-6 and IL-10). The treatment with HdLP 2,0% was able to decrease the polymorphonuclear infiltrate and increase the mononuclear on the 2nd day but had no effect on mast cell degranulation process in any period observed 2, 7 and 9 days. In the inflammatory phase, HdLP 2,0% decreased the MPO activity, confirming the reduction of migration of polymorphonuclear cells, and stimulated release of IL-1 β and IL-10 on day 2, moreover, the nitrite levels were reduced at 2 and 4 days and exalted on the 9th day. During the proliferative phase, HdLP 2,0% stimulated fibroplasia at 7 and 9 days after surgery, which probably contributed to increased collagen deposition observed in the 9th and 14th day. As the macroscopic analysis previously described, HdLP 2,0% favored the re-epithelialization process of excisional wounds but did not affect the thickness of newly formed epithelium. Therefore, all the results presented show that topical treatment with HdLP 2,0% modulates the inflammatory response of wound healing, influencing the subsequent phases and speeding up the tissue repair of experimental wounds excised.